Genesis of the Xishadegai Mo deposit in Inner Mongolia, North China: Constraints from geology, geochronology, fluid inclusion, and isotopic compositions. (19th February 2018) - Zhang, Yong‐Mei; Gu, Xue‐Xiang; Sun, Xuan; Zhao, Wei; Xiang, Zhong‐Lin; Liu, Rui‐Ping
Abstract : The Xishadegai Mo deposit is a medium‐sized deposit located in the northern margin of the North China Craton. The Mo mineralization is structurally controlled, and spatially and temporally related to the Xishadegai felsic intrusive rocks. Ore bodies mainly occur as quartz veins/veinlets in altered granitic rocks associated with potassic, phyllic, argillic, and fluorite alterations. The ore‐forming process can be divided into 3 stages: Stage I K‐feldspar‐quartz ± molybdenite, Stage II quartz‐pyrite‐molybdenite‐muscovite ± fluorite, and Stage III quartz‐fluorite ± muscovite. Four types of fluid inclusions were distinguished in smoky grey and dark grey quartz of the main‐ore stage (II), including two‐phase aqueous inclusions, CO2 ‐H2 O inclusions, daughter mineral‐bearing multiphase inclusions, and minor vapour aqueous inclusions. The fluid inclusions in smoky grey and dark grey quartz are homogenized at temperatures of 195–350 °C and 191–291 °C, respectively, with calculated salinities of 3.9–11.1% NaCleq and 31.5–33.0% NaCleq, respectively. The ore‐forming fluids belong to a H2 O‐CO2 ‐NaCl system characterized by abundant CO2, moderate to high temperature, and low to high salinity. The δ 18 OH2O and δD values of ore‐stage quartz vary from −0.2‰ to 0.9‰ and from −120‰ to −104‰, respectively, indicating that the ore‐forming fluids were evolved from magmatic water and gradually mixed with significant amounts of meteoric water. Sulphur and lead isotopic compositions indicate that the ore materials were mainly derived from magmatic sources. Zircon LA‐ICP‐MS U–Pb dating on the mineralized porphyritic moyite yielded a weighted mean age of 235.1 ± 2.0 Ma, corresponding to the Triassic postcollisional setting following the closure of the Paleo‐Asian Ocean between the Siberian Plate and the North China Craton. The εHf (t) values and TDM2 ages range from −15.0 to −12.8 and from 2.2 to 2.1 Ga, respectively, suggesting that the Xishadegai granite was mainly generated by melting of Paleoproterozoic crustal components. Collectively, evidence from geology, fluid inclusion, H‐O‐S‐Pb isotopes, and geochronology suggests that the Xishadegai deposit could be classified as a magmatic–hydrothermal vein Mo deposit. Phase separation (immiscibility and boiling) was the most likely mechanism for ore deposition.